2008
DOI: 10.1001/jama.2008.649
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Poor Glycemic Control and 9p21 Locus on Risk of Coronary Artery Disease in Type 2 Diabetes

Abstract: Context A common allele on chromosome 9p21 has been repeatedly associated with increased risk of coronary artery disease (CAD) in the general population. However, the magnitude of this effect in the population with diabetes has not been well characterized. Objective To examine the association of the 9p21 variant with CAD in individuals with type 2 diabetes and evaluate its interaction with poor glycemic control. Design, Setting, and Participants 1. Case-control study of 734 type 2 diabetic patients (322 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 41 publications
8
100
1
Order By: Relevance
“…Recently, a similar interaction has been observed between the 9p21 locus and poor glycemic control on the risk of CAD. 38 These findings demonstrate the complex interactions between genetic factors and traditional CAD risk factors in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, a similar interaction has been observed between the 9p21 locus and poor glycemic control on the risk of CAD. 38 These findings demonstrate the complex interactions between genetic factors and traditional CAD risk factors in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 81%
“…As personalization of chronic disease care increases in the coming era of genomic medicine, EHR-embedded clinical decision support may become an essential tool needed to systematically process complex risk prediction data and then accurately identify appropriate clinical goals and high-priority treatment options for each patient at each clinical encounter. 36,37 In this study, the use of EHR-based clinical decision support technology was reinforced by changes in clinic rooming procedures, changes in nurse roles, and provision of incentives to physicians and clinic staffelements that were lacking in previous failed attempts to implement EHR-based clinical decision support. Physicians were provided clinical decision support information immediately before the start of the visit to facilitate visit planning.…”
Section: Discussionmentioning
confidence: 93%
“…Several prospective studies have shown that chromosome 9p21 variation was associated with development of atherosclerosis and incident cardiovascular disease (14)(15)(16). However, Chen et al revealed that 9p21 conferred null effects on the severity or progression of coronary atherosclerosis in Caucasians (17).…”
Section: Discussionmentioning
confidence: 99%